Imperfection sensitivity of cylindrically curved steel panels. (April 2015) - Martins, J.P.; Beg, Darko; Sinur, Franc; Simões da Silva, L.; Reis, A.
Abstract: Unstiffened cylindrically curved panels constitute a common subset of shell structures and therefore share the advantages and disadvantages of such structural solution. One of the bigger disadvantages of shells is their sensitivity to imperfections that lower significantly their ultimate strength. At the European level, in the scope of plate design by FEM, imperfections are treated in EN 1993-1-5 (Annex C) and in shell structures designed by global numerical analysis using GMNIA, recommendations are given in EN 1993-1-6 (clause 8.7.2). Since curved panels are neither flat nor full revolution cylinders, rules for estimating equivalent geometric imperfections remain unclear. In order to tackle this problem, this paper introduces a numerical parametric study on the imperfection sensitivity of cylindrically curved panels. The effect of the amplitude and shape of initial geometric imperfections (together with different values of curvature and aspect ratio) on the ultimate strength of unstiffened cylindrically curved steel panels is studied, results are presented and conclusions are drawn. Highlights: Comprehensive study on how geometric imperfections act on the ultimate strength of cylindrically curved panels. Past and current approaches for the determination of geometric imperfections (patterns and amplitudes) are discussed. Proposal of formulae to calculate the maximum amplitude of equivalent geometric imperfections.